TELAAH LITERATUR MEDIA VIDEO PEMBELAJARAN TERHADAP MOTIVASI BELAJAR IPA SISWA SEKOLAH DASAR - Anggi Nadiya; Uvia Nursehah; Avi Valentri (LPPM Universitas Cipta Mandiri, 2025)
Low student motivation in science learning and the suboptimal use of engaging media remain key challenges in the teaching and learning process at the elementary school level. Conventional approaches that are still widely applied tend to overlook affective aspects that play a crucial role in student engagement. This study aims to analyze the use of instructional video media in enhancing elementary school students’ motivation to learn science through a literature review of various scholarly sources. Data were analyzed using content analysis on ten journal articles focusing on the variables of video media and learning motivation. The findings indicate that instructional video media consistently contributes positively to improving students’ learning motivation, particularly through the visual, interactive, and contextual presentation of material. The study concludes that video media holds strategic potential as a learning tool that is not only informative but also capable of stimulating students’ interest and engagement in science learning. These findings imply the importance of integrating instructional videos in a well-planned manner within learning design and encourage the development of digital learning media that align with the characteristics and learning needs of elementary school students.